Microhardness and elemental analysis of ion-releasing restoration/ dentin interface following enzymatic chemomechanical caries excavation - Rana E. Al-Wakeel; Hamdi H. Hamama; Dina S. Farahat; SA El-Negoly (BMC, 2024)
Abstract Background This study was conducted to compare chemical, elemental and surface properties of sound and carious dentin after application of two restorative materials resin-modified glassionomer claimed to be bioactive and glass hybrid restorative material after enzymatic chemomechanical caries removal (CMCR) agent. Methods Forty carious and twenty non-carious human permanent molars were used. Molars were randomly distributed into three main groups: Group 1 (negative control) - sound molars, Group 2 (positive control) - molars were left without caries removal and Group 3 (Test Group) caries excavated with enzymatic based CMCR agent. After caries excavation and restoration application, all specimens were prepared Vickers microhardness test (VHN), for elemental analysis using Energy Dispersive Xray (EDX) mapping and finally chemical analysis using Micro-Raman microscopy. Results Vickers microhardness values of dentin with the claimed bioactive GIC specimens was statistically higher than with glass hybrid GIC specimens. EDX analysis at the junction estimated: Calcium and Phosphorus of the glass hybrid GIC showed insignificantly higher mean valued than that of the bioactive GIC. Silica and Aluminum mean values at the junction were significantly higher with bioactive GIC specimens than glass hybrid GIC specimen. Micro-raman spectroscopy revealed that bioactive GIC specimens showed higher frequencies of v 1 PO 4, which indicated high level of remineralization. Conclusions It was concluded that ion-releasing bioactive resin-based restorative material had increased the microhardness and remineralization rate of carries affected and sound dentin. In addition, enzymatic caries excavation with papain-based CMCR agent has no adverse effect on dentin substrate.